PENGGUNAAN MEDIA ULAR TANGGA UNTUK KETERAMPILAN DASAR BERMAIN BOLA BASKET - Sobarna, Akhmad; Prasetyo, Aditya; Gunawan, Dicky (Jurnal Olahraga, 2019)
The purpose of this study was to find out how much influence the use of snake ladder media in improving students' dribbling skills in basketball games at the IT Tourism Vocational School Nurul Imam. With a sample of XI class of 30 people consisting of 18 female students and 12 students, the research method used experiments with the design of The Randomize Pretest-Posttest Control Group Design. Treatment given is in the form of snake ladder playing media in the learning process. The research process lasted for 5 weeks with the results of the analyst showing the average value obtained by students at the IT Tourism Vocational School Nurul Imam when the pre-test was conducted at 22.33 and the post-test was 26.56. there is an increase even though it is not too large with an average increase of 4.2.